HADIS TENTANG LARANGAN MENGAMBIL SESUATU SELAIN DARI UPAH KERJA YANG TELAH DITENTUKAN - Jamaluddin Abdullah (AL-IQTISHAD, 2020)
AbstractHadith narrated by Abu Dawud in his Sunan book, namely the hadith regarding the probhition of taking something apart from the predetermined wage, namely (a) it describes the obligation for a person who employs another person to give him a reward. It also explains the existence of the right of a person entrusted with a job or responsibility to get a pre-determined pay, (b) and it explains the prohibition for a person hired not to betray by taking things more than his right in sneaky way because the property will be distributed to each of  which is entitled, and (c) this hadith is more directed to the leaders and the government that they only take the right (wages) and they just do not do corruption and collusion because they are betrayal to the people they lead, given that must be distributed for the common good. Kata Kunci: Larangan; UpahKerja.